Effect of Gd3+ ion on silver zinc borate glasses - K.M. Shwetha; B Eraiah (Chemical Physics Impact)
The conventional melt quenching technique approach has been used to create glasses with the composition of ZnO-B2O3-Gd2O3-Ag2O.Using the X-ray diffraction technique, the synthesized glasses have been characterized. Using the Archimedes method, the density and molar volume were calculated. To record the absorption spectra, a UV–visible spectrometer was employed, the energy band gap has been evaluated using Tauc's plots. The variation of band gap energies related to Gd2O3 concentration has been discussed. FTIR spectra are examined to determine the sample's structure and functional group. When the Gd3+ ion is added to the doped glass, the photo luminescence spectra produces a consistent orange-red emission, as evidenced by the colour coordinates obtained from the CIE diagram.